Knowledge management and empowering leadership affect employee performance mediated by employee development in PT. Bina Rekacipta Utama Jakarta Selatan - Anggapradja, Indra Taruna; Agustriyana, Darwis; Faritzal, Adam (Gema Wiralodra, 2024)
Directly or indirectly, employee performance impacts the sustainability of all company activities, which various factors can influence. This study aims to find out how to test knowledge management and empowering leadership on employee performance through employee development at PT. Bina Rekacipta Utama, South Jakarta. The research method used in this study is a quantitative approach to determine the relationship between variables in a population. While the sample used in this study is all employees who work at PT. Bina Rekacipta Utama, South Jakarta. This research uses multiple regression with Moderated Regression Analysis (MRA) to determine the effect of knowledge management and empowering leadership on employee performance mediated by employee development. Based on the research results, it was found that knowledge management and empowering leadership had a significant effect on employee performance through employee development as a mediating variable at PT. Bina Rekacipta Utama, South Jakarta. The research results are expected to have implications for implementing better knowledge management and creating independent leadership to improve employee and company performance. Employee development must also be an organization concern because it dramatically influences the overall performance of employees. Employees who have confidence in their career development will be more satisfied at work.